2016
DOI: 10.1186/s12986-016-0152-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of controlled doses of Oxyelite Pro on physical performance in rats

Abstract: BackgroundOxyElite Pro (OEP) is a dietary supplement to increase metabolism which contains as key stimulant the ingredient 1,3-dimethylamylamine (DMAA). Serious adverse effects have been reported after OEP consumption however, these effects are related to poisoning or overdose. To our knowledge, no one studied the effects of OEP at controlled doses. Thus, the aim of this study was to evaluate acute and chronic OEP affects, at controlled doses in Wistar rats, on physical performance, metabolic parameters, liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For example, a randomized, double-blind, placebo-controlled, 12-week study in healthy men administered 1,3-dimethylamylamine alone or in combination with caffeine, found no change in markers of oxidative stress, including malondialdehyde (MDA), advanced oxidation protein products (AOPP) and trolox equivalent antioxidant capacity (TEAC) [77]. Wistar rats given a dietary supplement containing 1,3-dimethylamylamine in fact showed evidence of an anti-oxidative effect including decreases in thiobarbituric acid reactive substances (TBARS) and AOPP [78]. This can be contrasted with the increase in markers of oxidative stress (e.g., TBARS) in rat liver cells and in humans (e.g., MDA) who are chronic users of methamphetamine [[79], [80], [81], [82]].…”
Section: Mechanism Of Amphetamine-induced Hepatotoxicitymentioning
confidence: 99%
“…For example, a randomized, double-blind, placebo-controlled, 12-week study in healthy men administered 1,3-dimethylamylamine alone or in combination with caffeine, found no change in markers of oxidative stress, including malondialdehyde (MDA), advanced oxidation protein products (AOPP) and trolox equivalent antioxidant capacity (TEAC) [77]. Wistar rats given a dietary supplement containing 1,3-dimethylamylamine in fact showed evidence of an anti-oxidative effect including decreases in thiobarbituric acid reactive substances (TBARS) and AOPP [78]. This can be contrasted with the increase in markers of oxidative stress (e.g., TBARS) in rat liver cells and in humans (e.g., MDA) who are chronic users of methamphetamine [[79], [80], [81], [82]].…”
Section: Mechanism Of Amphetamine-induced Hepatotoxicitymentioning
confidence: 99%
“…However, chronic administration (4 weeks) of the supplement impaired exercise performance. The authors concluded the supplement had acute stimulant-like effects on rodents consistent with the pharmacological profile of DMAA and its reported acute effects in man ( 19 ) . In another rodent study, DMAA produced effects on behaviour similar to those produced by cocaine and to a lesser extent methamphetamine ( 20 ) .…”
mentioning
confidence: 63%
“…Several animal studies have been conducted to examine various effects of DMAA ( 19 , 20 ) . In one rodent study, acute administration of a DMAA-containing supplement increased running time and distance ( 19 ) . However, chronic administration (4 weeks) of the supplement impaired exercise performance.…”
mentioning
confidence: 99%
“…Our results showed that the concentration of 100 mg/L of DMAA caused an increase in antioxidant levels. A recent study [42] showed that supplements containing DMAA led to an increase in antioxidant parameters of rat soleus muscle and liver. Caffeine treatment also caused a significant increase in the antioxidant level of lymphocytes compared to the control.…”
Section: Discussionmentioning
confidence: 99%